2002
DOI: 10.1001/archinte.162.14.1636
|View full text |Cite
|
Sign up to set email alerts
|

Successful Blood Pressure Control in the African American Study of Kidney Disease and Hypertension

Abstract: The blood pressure goals set and achieved in AASK participants clearly demonstrate that adequate blood pressure control can be achieved even in hypertensive populations whose blood pressure is the most difficult to control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
77
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(78 citation statements)
references
References 19 publications
0
77
0
1
Order By: Relevance
“…First, although African Americans with CKD represent an important population for study, our findings cannot necessarily be extrapolated to nonblack patients with CKD or those whose renal disease is caused by other etiologies. Second, BP control in the AASK study was superior to that observed in many other trials and likely the general population (36). Although this also may somewhat detract from the generalizability of our findings, the attention paid to participants in AASK increases the internal validity of our findings by limiting the effect of external factors on SBV.…”
Section: Discussionmentioning
confidence: 56%
“…First, although African Americans with CKD represent an important population for study, our findings cannot necessarily be extrapolated to nonblack patients with CKD or those whose renal disease is caused by other etiologies. Second, BP control in the AASK study was superior to that observed in many other trials and likely the general population (36). Although this also may somewhat detract from the generalizability of our findings, the attention paid to participants in AASK increases the internal validity of our findings by limiting the effect of external factors on SBV.…”
Section: Discussionmentioning
confidence: 56%
“…The protocol and procedures were approved by the institutional review board at each center, and all participants gave written informed consent (10,11).…”
Section: Methodsmentioning
confidence: 99%
“…We use data from the recently completed AASK to evaluate whether use of serum creatinine measurements (or estimated GFR from equations based on serum creatinine measurements) would alter any of the primary conclusions of the study compared with the conclusions reached on the basis of direct measurements of 125 I-iothalamate GFR (iGFR) (10,11). The comparison of iGFR with serum creatinine-based results was performed for three types of analysis.…”
mentioning
confidence: 99%
“…11 However, patients with high values of MAP, proteinuria or SCr were excluded from the MDRD study, which may explain the difference. In the recently published African American Study of Kidney Disease and Hypertension (AASK) 12 the degree of BP goal achievement was considerably higher than in the Blood pressure control in chronic renal failure T Giverhaug et al present study. However, the included patients were younger, healthier and probably more adherent to their drug therapy than ours, as only self-identified patients with impaired renal function due to essential hypertension were included.…”
Section: Bp and Goal Achievementmentioning
confidence: 53%
“…12 However, a comparison of the number of drugs required is of limited value without ensuring that optimal dose titration has been performed and that comorbidity has been taken into account. In the AASK study, 12 the dosage of each AHT was titrated to the maximum tolerated dose before adding a new agent. In the present study, some of the patients suffered from heart diseases and were probably prescribed drugs here defined as AHT for indications other than hypertension.…”
Section: Antihypertensive Medication and Prescription Patternsmentioning
confidence: 99%